The role of motivation: the effect of transformational leadership on employee performance - Piedade, Salustiano Dos Reis; Wardana, I Made; Riana, Gede; Dewi, I Gusti Ayu Manuati (International research journal of management, IT and social sciences, 2019)
The purpose of this study was to examine the mediating role of the influence of transformational leadership on employee performance. The research was conducted at the Ministry of Education of Timor-Leste with a total population of 765 and a sample size of 263 respondents. Data were analyzed by using Smart-PLS 3.0 Program software. The results showed that transformational leadership was positively and significantly related to employee performance. Motivation plays a role in mediating the effect of transformational leadership on employee performance.